Literae Cantuarienses: The Letter Books of the Monastery of Christ Church, Canterbury. - Sheppard, J. (Cambridge library collection. Rolls, 1888)
Christ Church, Canterbury, was the seat of the archbishop and an important pilgrimage site. The letters and other documents in its register reveal not only its history, but how complex was the management of the priory and its estates. This three-volume edition is based on a transcript of the register compiled in 1411. Volume 2, edited by Joseph Brigstocke Sheppard (1827–95) and published in 1888, contains items 495–943, ranging in date from 1333 to 1373. The editor has selected documents addressed to individuals or groups, and the subjects vary widely. Most relate to church affairs and include formal letters of appointment and disputes with other monasteries. Others are financial, dealing with rents, taxes and donations by important pilgrims. Also covered are matters of national importance (as the prior sat in parliament), such as the Hundred Years' War and the Black Death. The texts are in Latin, Norman French and English, with translations provided for the French documents.